Karakteristik Rebon Kering Pada Pembuatan Serundeng Ampas Tahu - Rabiah, Rabiah; Nurwidah, Andi; Inayah, Astrina N (Universitas Pattimura, 2025)
Tofu dregs are a solid waste generated during the tofu production process, but they can be repurposed as food due to their rich nutritional content, including protein and minerals. One innovative use of tofu pulp is to process it into serundeng (a flaked coconut dish). To enhance the nutritional quality, particularly the protein content, dried shrimp (rebon), which is rich in protein, can be added. This study aims to determine the impact of adding dried shrimp on the moisture content, protein content, yield, and the processing method based on sensory evaluation, such as color, aroma, taste, and texture. The method used was a completely randomized design with four treatments and three replications: A (0% dried shrimp), B (5% dried shrimp), C (10% dried shrimp), and D (15% dried shrimp). Adding dried shrimp significantly affected the moisture and protein content but did not significantly affect the yield. The highest moisture content was found in treatment A (0%) at 18.63% and tended to decrease with the increase of dried shrimp due to its dry nature. Conversely, the protein content increased with the addition of dried shrimp, with the highest value in treatment D (15%) at 26.20%. The highest yield was recorded in treatment C (10%) at 22.77%, but the differences between treatments were not statistically significant. Each attribute showed a different best treatment based on the sensory evaluation results. Treatment A (0%) scored the highest for the color attribute at 4.20, indicating that the panelists preferred the panelists most preferred the product without dried shrimp addition. The best taste was found in treatment D (15%) with a score of 4.27, while the best aroma was found in treatment C (10%) with a score of 4.11. Treatment C (10%) scored the highest for the texture attribute at 4.23, indicating the most preferred texture. Treatment C (10%) was considered the most balanced regarding taste, aroma, and texture, making it the best formulation regarding panelist preference.